Flexed radiographic angles for determination of atlantoaxial instability in dogs. Issue 8 (10th September 2019) - White, Dana A.; Renberg, Walter C.; Roush, James K.; Hallman, Mackenzie R.; Mauler, Daniela A.; Milliken, George A.
Abstract: Objective: To determine a flexed position for radiographic diagnosis of atlantoaxial instability (AAI) and to identify radiographic measurement cutoffs to differentiate affected dogs from neurologically healthy toy breeds. Study design: Retrospective case series and prospective case controls. Animals: Thirty‐nine client‐owned toy breed dogs in which AAI had been diagnosed and 20 neurologically healthy client‐owned toy breed dogs. Methods: Medical records from three institutions were retrospectively reviewed to identify dogs affected with AAI. Flexed lateral images were reviewed, and measurements were obtained by using anatomic landmarks. Radiography was performed with control dogs to obtain the same measurements. Results: Flexed lateral radiographs of thirty dogs affected with AAI were found to be positioned at a mean of 51° flexion. When flexed lateral radiographs were evaluated with a cutoff value for atlas to axis angle (AAA) >10°, evaluation of all breeds represented revealed a 90% sensitivity and 90% specificity. When this cutoff was evaluated in Yorkshire terriers, Chihuahuas, and mixes of these breeds, the sensitivity was 92%, and the specificity was 92%. When the control sample was positioned at 51° ± 10°, only two of the dogs were within the AAA cutoff value of >10°. There was no difference between the measurements obtained by using the flexed lateral view (mean = 50.9°) and the exaggerated flexed lateral view (mean = 38.9°) in the control sample. Conclusion: This study established objective measurements for the positioning and diagnosis of AAI on flexed lateral radiographs in toy breed dogs. Clinical significance: Atlantoaxial instability can be objectively diagnosed in sedated or anesthetized toy breed dogs when applying 51° flexion to cervical radiographs.